2004
DOI: 10.1074/jbc.m309375200
|View full text |Cite
|
Sign up to set email alerts
|

High Attenuation and Immunogenicity of a Simian Immunodeficiency Virus Expressing a Proteolysis-resistant Inhibitor of NF-κB

Abstract: NF-B/I B proteins play a major role in the transcriptional regulation of human immunodeficiency virus, type-1 (HIV-1). In the case of simian immunodeficiency virus (SIV) the cellular factors required for the viral transcriptional activation and replication in vivo remain undefined. Here, we demonstrate that the p50/p65 NF-B transcription factors enhanced the Tat-mediated transcriptional activation of SIVmac239. In addition, I B-␣S32/36A, a proteolysis-resistant inhibitor of NF-B, strongly inhibited the Tat-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…2), indicating that in the setting of HIV infection of primary monocytes NF-κB plays a non-redundant role. These results are in agreement with the evidence that IκB-αS32/36A negatively affected the replication of HIV and SIV in PBMC cultures and in monkeys [16,17]. …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…2), indicating that in the setting of HIV infection of primary monocytes NF-κB plays a non-redundant role. These results are in agreement with the evidence that IκB-αS32/36A negatively affected the replication of HIV and SIV in PBMC cultures and in monkeys [16,17]. …”
Section: Discussionsupporting
confidence: 92%
“…These findings supported an interpretation that in these cellular contexts NF-κB is required for efficient viral replication. We also showed that a recombinant SIV which expressed IκB-αS32/36A inhibitor was also highly replication attenuated in vivo in rhesus macaque [17]. Here, we have extended our analysis of IκB-αS32/36A function in HIV-1 replication to primary monocytes.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…To generate p3XFLAG-CMV-Tat, p3XFLAG-CMV-Tat C (22,25,27)A, and p3XFLAG-CMV-Tat R(49 -57)A, the sequence of Tat was amplified from the pGEX-2T-Tat expressing vectors (43) and ligated to EcoRI/XbaI-digested p3XFLAG-CMV-7.1 (Sigma). pRc/CMV-HA-I B-␣S32/36A was previously described (44). The plasmids expressing the I B-␣ mutants 120 -317, 1-280, 1-269, 1-242, 72-287, and 72-269 were generated by PCRmediated amplification of the I B-␣ sequence from pCMV4-HA-I B-␣ with appropriate forward and reverse primers followed by ligation to the HindIII/XbaI-digested pCMV4-HA.…”
Section: Methodsmentioning
confidence: 99%